From: K. Werckmeister (ed.), Das neunzehnte Jahrhundert in Bildnissen, Bd. III, Berlin 1899, no. 301 - Mason, ...
From: K. Werckmeister (ed.), Das neunzehnte Jahrhundert in Bildnissen, Bd. III, Berlin 1899, no. 301.